Influence of land use with cocoa crops, chakras and primary forest on diversity, carbon storage and productivity in Sumaco Biosphere Reserve, Ecuador - Jadán Maza, Angel O. (2012)
Tesis (Mag.Sc.) -- CATIE, 2012